Alto suprimento de nitrato atenua efeitos adversos da salinidade em mudas de cajueiro - Santos, Magna Pereira dos (2024)
The cashew tree (Anacardium occidentale L.) is a species native to the Northeast region of Brazil. Despite its great socioeconomic importance, this crop faces a series of environmental challenges such as high light, high temperatures, water scarcity and excess salts in the soil, resulting from the region's edaphoclimatic conditions. We tested the hypothesis that high NO3- supply might attenuate adverse effects caused by excess of Na+ and Cl- on the photosynthetic efficiency by stimulation of alternative electron sinks to nitrate assimilation. The experiment was conducted in a completely randomized design in a factorial scheme(2x2), in which cashew plantlets (species adapted to low soil nitrate and salinity in semiarid regions) were exposed to high salinity (NaCl 0 and 100 mM) in the presence of two contrasting NO3- levels, 0.1 mM (low) and 10.0 mM (high), for 35 days in greenhouse conditions. High nitrate supply stimulated leaf expansion and decreased root length in the absence of salinity, but did not affect these variables under saline stress. The high nitrate was able to reduce membrane damage associated with lower Na+ and Cl- accumulation and lower Na+/K+ ratios in leaves under saline stress. High nitrate content did not affect photosynthetic electron transport rates, while PSI acceptor side limitation decreased under salt stress. CO2 assimilation rates did not change due to the effect of nitrate levels. In contrast, photorespiration rates were increased by high nitrate in the absence of salinity, whereas, regardless of nitrate levels, salinity induced a prominent increase in photorespiration rates. Interestingly, when photorespiration was artificially abolished or intensely decreased by O2 scavenging, high NO3- induced large increases in Vcmax, Jmax and PNmax in salt stressed plants.The high supply of NO3- is capable of mitigating some adverse effects of salinity on cashew plantlets. The photorespiration is the largest alternative electron sink compared to the use of nitrate, which could be more important in situations of low photorespiration.